Relasi Budaya dan Kuasa dalam Konstruksi Islam Kultural Pasca-Reformasi - M. Qomarul Huda (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2013)
This article discusses the cultural construction of post-reform Islam has offered a variety of opportunities and challenges. Through content analysis and social hermeneutics (which is defined as a personal interpretation of the human as a social action, this study detects that the construction of the Islamic cultural post-reform is a form of political responses to Islamic culture. Through cultural ideology, politicians take advantage of the cultural basis for the crawl political interests at the same time releasing its cultural organizations from the burden of political stigmatization that could happen someday. kulturalisasi Also the political process that the political process without developing Islamic symbols. Bid with culture-based politics is beneficial but at the same harm on the other.